The Use of Bioelectrical Impedance to Assess Shelf-Life of Beef Longissimus Lumborum Steaks - F. Najar-Villarreal; E. A. Boyle; T. A. Houser; C. I. Vahl; J. Wolf; J. M. Gonzalez; T. G. O'Quinn; J. Kastner; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:The objective of this study was to evaluate the efficacy of using surface and internal bioelectrical impedance to assess beef longissimus lumborum shelf-life during 15 days of simulated retail display. Study Description:Beef strip loins, obtained from three commercial processors (postmortem age = 27, 34, or 37 days), were fabricated into 12 1-inch thick steaks. Steaks were subdivided into six consecutively cut pairs, packaged on Styrofoam trays, overwrapped with polyvinyl chloride film, and displayed under fluorescent lighting at 32–40°F in coffin-style retail cases for 15 days. Microbiological analysis, pH, bioelectrical impedance analysis, objective color assessment, proximate composition, and lipid oxidation were measured. Surface and internal bioelectrical impedance assessment were compared. The BottomLine:Internal bioelectrical impedance has potential for use to assess shelf-life of retail steaks and it was more precise than surface bioelectrical impedance; however, internal bioelectrical impedance may translocate bacteria into the muscle. Protein degradation and water holding capacity should be evaluated to better understand bioelectrical impedance changes over time.
Keywords: impedance; longissimus; shelf-life